Defying carceral logics in technology-facilitated sexualized violence: technological, legal, and intersectional progress - Oswald, Flora (Contemporary justice review, 2024)
Technology-facilitated sexualized violence (TFSV) refers to a broad range of sexually aggressive behaviors mediated by or otherwise involving technology. The severe consequences of TFSV victimization, including victim-survivor suicidality, are particularly salient among marginalized populations (e.g. women of color) and render TFSV a source of emerging public concern. Correspondingly, an emerging literature provides recommendations for best preventing and responding to TFSV. At the forefront of this literature are carceral responses, which turn to institutionalized power structures (e.g. police, criminal justice systems) to manage TFSV. We argue that this turn to carceral responses mirrors decades of dominant (white) feminist ignorance of links between state and individual violence, and argue that carceral approaches are fundamentally incapable of reducing harm among oppressed peoples. We forward abolitionist approaches to TFSV responding which acknowledge TFSV’s interconnectedness with broader systems of oppression and disrupt reliance on state-sanctioned forces. We argue that abolitionist responses are inherently more capable of addressing root causes of TFSV and producing transformative justice, particularly for members of (multiply) marginalized groups. Opportunities for abolitionist experimentation in TFSV responding are highlighted, with a particular focus on avenues that transform the cyber-context from the site of harm to a site of resistance, collaboration, and care.